The Effect of Tideglusib Application on Type 1 and Type 3 Collagen Expressions by Human Dental-Pulp Derived Stem Cells: A Preliminary Study. - AĞRALI, ÖMER BİRKAN (My University, 2024)
Background: Although Tideglusib cytotoxicity studies and its effects on human dental pulp‑derived stem cells (DPSCs) have been examined in previous studies, there is no study investigating the expression of type 1 collagen and type 3 collagen by Tideglusib. Aim: The purpose of this study is to examine the effect of Wnt signaling activation using Tideglusib execution on human DPSC to determine its potential efficacy in collagen expression. Methods: Stem cell isolation was performed from five human third molar wisdom tooth pulps. DPSCs identified in only one sample were treated with 50 nM Tideglusib for 24 h and 1 week. Axin‑2, type 1 and type 3 collagen expressions were evaluated by Western blot analysis. DPSCs without treatment served as a negative control. The Mann‑Whitney U test was used for statistical analysis. Results: The levels of type 1 collagen and Axin‑2 in the test group were significantly higher than those in the control group at 24 h (P = 0.000, P = 0.001, respectively). Compared to the control group, a slight increase in type 3 collagen expression was observed in the test group at 24 h (P value = 0.063). Application of 50 nM Tideglusib for 1 week revealed marked decreases in type 1 and type 3 collagen expressions (P = 0.029, P = 0.038, respectively). In contrast, there was a significant increase in the level of Axin‑2 (P = 0.000) compared to the control group. Conclusion: The fact that Wnt signaling pathway activation obtained by Tideglusib application on DPSCs confirmed by the finding in the increase of Axin‑2 at short and long‑term evaluation periods which is resulted in the increase in the type 1 collagen expression at 24 h and decrease at 1 week together with the decrease in type 3 collagen expression at 1 week warrants further studies to evaluate the effect of Tideglusib on extracellular matrix expression. Keywords: Dental pulp, GSK‑3 inhibitor, periodontal regeneration, stem cell, Tideglusib, Wnt signaling pathway
Keywords: Dental pulp; GSK‑3 inhibitor; periodontal regeneration; stem cell; Tideglusib; Wnt signaling pathway